2023
DOI: 10.18632/aging.204459
|View full text |Cite
|
Sign up to set email alerts
|

The pan-cancer analysis identified DIAPH3 as a diagnostic biomarker of clinical cancer

Abstract: Objective: This study aimed to determine prognostic biomarkers of cervical cancer by pan-cancer analysis. Materials and Methods: Common differentially expressed genes in Gene Expression Omnibus and The Cancer Genome Atlas (TCGA) database were demonstrated using R software analysis, and these genes were enriched by the Kyoto Encyclopedia of Genes and Genomes and Gene Ontology. Genes with prognostic value were identified by least absolute contraction and selection regression, Cox regression, and survival analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…miRNA-363-3p overexpression inhibits proliferation, invasion and metastasis of thyroid cancer cells, which is reversed by SYT1 overexpression [ 30 ]. Increased expression of DIAPH3 in cervical cancer may be associated with proliferation of cervical cancer [ 31 ]. DIAPH3 expression is also associated with low survival of osteosarcoma patients and can promote proliferation and metastasis of osteosarcoma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-363-3p overexpression inhibits proliferation, invasion and metastasis of thyroid cancer cells, which is reversed by SYT1 overexpression [ 30 ]. Increased expression of DIAPH3 in cervical cancer may be associated with proliferation of cervical cancer [ 31 ]. DIAPH3 expression is also associated with low survival of osteosarcoma patients and can promote proliferation and metastasis of osteosarcoma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of cancer-related studies have previously documented a role of DIAPH3 in modulating tumor cell aggressiveness albeit in a context-and study-specific manner. For example, pan-cancer analyses revealed that DIAPH3 is upregulated in multiple types of human cancer (breast, cervical, head and neck squamous carcinoma, glioblastoma and several others) and serves as a prognostic manner in certain cancers (Chen et al, 2023). DIAPH3 expression is upregulated in osteosarcoma, and silencing DIAPH3 expression suppresses proliferation, migration/invasion and metastasis of osteosarcoma cells (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%